2011
DOI: 10.1128/jvi.05382-11
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of Basic Amino Acids in the Factor X Serine Protease Mediates Surface Attachment of Adenovirus/FX Complexes

Abstract: Hepatocyte transduction following intravenous administration of adenovirus 5 (Ad5) is mediated by interaction between coagulation factor X (FX) and the hexon. The FX serine protease (SP) domain tethers the Ad5/FX complex to hepatocytes through binding heparan sulfate proteoglycans (HSPGs). Here, we identify the critical HSPG-interacting residues of FX. We generated an FX mutant by modifying seven residues in the SP domain. Surface plasmon resonance demonstrated that mutations did not affect binding to Ad5. FX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…To exclude the possibility that adenovirus uses CAR to enter hepatocytes in the absence of heparan sulfate, we investigated the ability of the vector AdY477A, in which CAR binding is ablated, to transduce Ext1 HEP A substantial amount of experimental evidence indicates that Ad.FX can bind directly to heparin and to HS (6,23,24,43). Therefore, not surprisingly, heparin injected intravenously into mice immediately prior to Ad5 injection blocks liver uptake (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude the possibility that adenovirus uses CAR to enter hepatocytes in the absence of heparan sulfate, we investigated the ability of the vector AdY477A, in which CAR binding is ablated, to transduce Ext1 HEP A substantial amount of experimental evidence indicates that Ad.FX can bind directly to heparin and to HS (6,23,24,43). Therefore, not surprisingly, heparin injected intravenously into mice immediately prior to Ad5 injection blocks liver uptake (6).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ad5 binding to HSPGs requires the presence of blood coagulation factor X (FX), which binds to the Ad5 hexon when the virus comes in contact with blood (7,(21)(22)(23). The interaction of Ad.FX and HS is mediated by electrostatic interactions between the heparin binding exosite of the FX serine protease domain and the sulfate groups of HS (6,(23)(24)(25). FX is required for Ad5 transduction in vivo in wild-type mice.…”
mentioning
confidence: 99%
“…The mechanism is based on the fact that they bind to blood coagulation factor X upon injection into the blood stream. Factor X (bound to the vector particles) mediates a bridging to heparan surface proteoglycans (HSPGs) on the hepatocyte surface, and this triggers the uptake of viral particles by hepatocytes (Waddington et al 2008;Alba et al 2009;Bradshaw et al 2010;Duffy et al 2011). The bioluminescence recording of freely moving mice can only be performed on the dorsal side of animals, since the cage bottom is covered with nontransparent litter.…”
Section: Visualization Of Circadian Liver Gene Expression By Whole-bomentioning
confidence: 99%
“…In the FX SP domain, seven basic amino acids (R273, K276, R306, R347, K351, K420, and R424) have been shown to mediate surface attachment of HAdv-FX complexes to HSPGs on hepatocytes (32). Previous analyses identified that K420 and R424 are the most critical residues for heparin binding to FXa, and together with the other charged amino acids, they form the so-called heparin-binding exosite on the surface of the FX SP domain (33).…”
Section: Fvii Binds Hadv5 Hexon In An Altered Orientation Compared Tomentioning
confidence: 99%